How comfortable are Malaysian users in utilizing webpages of small businesses? - Abdullah, Moha Asri; Alom, Fardous; Juhdi, Nurita; Mohammad, Noorihsan; Azam, S.M. Ferdous (2014)
Online transaction for business and individual purchases is now becoming routine works for the users worldwide due to the inception, development and rapid expansion of World Wide Web in last three decades. The internet era in Malaysia started during the year 1995 and since then dramatic changes have taken place in terms of internet facilities and customers’ perceptions. The main objective of the current study is to explore the challenges the Malaysian consumers face in terms of e-commerce experiences with small businesses in general and, in particular, to identify the ranks of bad experiences they encounter within the framework of descriptive statistics and multiple regressions based on a questionnaire approach. In addition, the study also looks into the potential impacts of demographic profiles of respondents on the e-commerce experiences in general and bad experiences in particular using one way ANOVA. The results suggest that e-commerce users face highest challenges with after purchase services followed by overall quality, usage experience, value, and installation. Regarding bad experiences, slow internet appears on the top of the list followed by slow delivery of the products, unfriendly website, poor quality products, complicated payment system, and unsecured operations. Although many previous studies of the last decade identified that security concern is the top barrier of e-commerce adoption, this study reveals that security issue is no longer serious issue for Malaysian customers. The demographic characteristics such as gender, race and income have significant impacts on the level of satisfaction perceived in the e-commerce transaction while regarding bad experiences the demographic profiles have little or no impacts. The results of this study provide insights to the policymakers and business practitioners to address the issues of after purchase services and slow internet.